A class of versatile circuits, made up of standard electrical components, are memristors. (30th March 2015) - Ascoli, Alon; Corinto, Fernando; Tetzlaff, Ronald
Summary: In this paper, we propose a whole class of memristor circuits. Each element from the class consists of the cascade connection between a static nonlinear two‐port and a dynamic one‐port. The class may be divided into two subclasses depending on the input variable (voltage or current). Within each of these subclasses, two further sets of memristor circuits may be distinguished according to which output voltage and current of the two‐port represents one of the system states. The simplest memristor circuits make only use of purely passive elementary components from circuit theory, an absolute novelty in this field of research. Thus they are suitable circuit primers for the introduction of the topic of memristors to undergraduate students. A sample circuit is built using discrete devices and its memristive nature is validated experimentally. In case the one‐port is purely passive, the proposed circuits feature volatile memristive behavior. Allowing active devices into the dynamic one‐port, non‐volatile dynamics may also emerge, as proved through concepts from the theory of nonlinear dynamics. Given the generality of the proposed class, the topology of the emulators may be adjusted so as to induce a large variety of dynamical behaviors, which may be exploited to accomplish new signal processing tasks, which conventional circuits are unable to perform. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : This manuscript proves analytically and confirms through a number of numerical simulations and lab experiments that a wide and novel class of circuits, consisting of the cascade between a static nonlinear two‐port and a dynamic one‐port, act as memristors with access nodes given by the input terminals of the two‐port. In general, the proposed memristors are volatile and, in their simplest realization, are composed solely of purely passive electrical components. More interesting behaviors, including non‐volatility, exploitable for the development of novel signal processing applications, may emerge by suitable design of the proposed circuit structures.